A needs assessment of health information technology for improving care coordination in three leading patient-centered medical homes. (21st March 2015) - Richardson, Joshua E; Vest, Joshua R; Green, Cori M; Kern, Lisa M; Kaushal, Rainu; ,
Abstract: Objective We investigated ways that patient-centered medical homes (PCMHs) are currently using health information technology (IT) for care coordination and what types of health IT are needed to improve care coordination. Materials and Methods A multi-disciplinary team of researchers conducted semi-structured telephone interviews with 28 participants from 3 PCMHs in the United States. Participants included administrators and clinicians from PCMHs, electronic health record (EHR) and health information exchange (HIE) representatives, and policy makers. Results Participants identified multiple barriers to care coordination using current health IT tools. We identified five areas in which health IT can improve care coordination in PCMHs: 1) monitoring patient populations, 2) notifying clinicians and other staff when specific patients move across care settings, 3) collaborating around patients, 4) reporting activities, and 5) interoperability. To accomplish these tasks, many participants described using homegrown care coordination systems separate from EHRs. Discussion The participants in this study have resources, experience, and expertise with using health IT for care coordination, yet they still identified multiple areas for improvement. We hypothesize that focusing health IT development in the five areas we identified can enable more effective care coordination. Key findings from this work are that homegrown systems apart from EHRs are currently used to support care coordination and, also, that reporting tools are key components of care coordination. Conclusions New health IT that enables monitoring, notifying, collaborating, reporting, and interoperability would enhance care coordination within PCMHs beyond what current health IT enables.